Common Trends and Structural Change : A Dynamic Macro Model for the Pre- and Postrevolution Islamic Republic of Iran - Becker, Torbjorn (Washington, D.C. : International Monetary Fund, 1999)
This paper uses a common trends model to study how prices, the black market exchange rate, money, and real output have developed over a period covering both pre- and post-revolution Iranian data. It is shown that monetary shocks have significant short-run effects on output, but permanent effects on the price level and exchange rate, that is, expansionary monetary policy is not consistent with achieving low inflation or a stable unified exchange rate. The real shocks generate higher growth and lower inflation, suggesting that supply-side policies are consistent with the goals in the Islamic Republic of Iran's second five-year development plan.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet